Characterization of experimental diabetic neuropathy using multicontrast magnetic resonance neurography at ultra high field strength - Schwarz, Daniel; Hidmark, Asa S.; Sturm, Volker Jörg Friedrich; Fischer, Manuel; Milford, David; Haußer-Siller, Ingrid; Sahm, Felix; Breckwoldt, Michael O.; Agarwal, Nitin; Kuner, Rohini; Bendszus, Martin; Nawroth, Peter Paul; et al. (Scientific reports, 2020)
In light of the limited treatment options of diabetic polyneuropathy (DPN) available, suitable animal models are essential to investigate pathophysiological mechanisms and to identify potential therapeutic targets. In vivo evaluation with current techniques, however, often provides only restricted information about disease evolution. In the study of patients with DPN, magnetic resonance neurography (MRN) has been introduced as an innovative diagnostic tool detecting characteristic lesions within peripheral nerves. We developed a novel multicontrast ultra high field MRN strategy to examine major peripheral nerve segments in diabetic mice non-invasively. It was first validated in a cross-platform approach on human nerve tissue and then applied to the popular streptozotocin(STZ)-induced mouse model of DPN. In the absence of gross morphologic alterations, a distinct MR-signature within the sciatic nerve was observed mirroring subtle changes of the nerves’ fibre composition and ultrastructure, potentially indicating early re-arrangements of DPN. Interestingly, these signal alterations differed from previously reported typical nerve lesions of patients with DPN. The capacity of our approach to non-invasively assess sciatic nerve tissue structure and function within a given mouse model provides a powerful tool for direct translational comparison to human disease hallmarks not only in diabetes but also in other peripheral neuropathic conditions.